2016
DOI: 10.3892/etm.2016.4003
|View full text |Cite
|
Sign up to set email alerts
|

Casticin inhibits the activity of transcription factor Sp1 and the methylation of RECK in MGC803 gastric cancer cells

Abstract: Abstract. The present study investigated the effect of casticin on reversion-inducing-cysteine-rich protein with kazal motifs (RECK) gene expression and intracellular methylation levels in MGC803 gastric cancer cells. Cells were treated with 1, 10 and 30 µmol/l casticin. Western blotting and reverse transcription-quantitative polymerase chain reaction assays were performed to determine the protein expression and mRNA levels of RECK and DNA methyltransferase 1 (DNMT1), respectively. High-performance liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Furthermore, we have reported that casticin was cytotoxic for cancer cells; decreased the total number of viable cells, induced cell cycle arrest, and apoptosis of SCC-4 cells in vitro. These findings are in agreement with other reports indicating that casticin suppresses the proliferation of different tumor cells (11,22,35,36). Importantly, casticin had no effects on cell proliferation and prolactin release in nonstimulated primary pituitary cells in vitro (17).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we have reported that casticin was cytotoxic for cancer cells; decreased the total number of viable cells, induced cell cycle arrest, and apoptosis of SCC-4 cells in vitro. These findings are in agreement with other reports indicating that casticin suppresses the proliferation of different tumor cells (11,22,35,36). Importantly, casticin had no effects on cell proliferation and prolactin release in nonstimulated primary pituitary cells in vitro (17).…”
Section: Discussionsupporting
confidence: 93%
“…DNMT1 plays an essential role in CSLC feature maintenance and frequently decreased miR-34a expression in CSLCs [1015, 2225]. So, we initially compared the DNMT activation as well as miR-34a expression and promoter methylation between OSLCs (the sphere-forming U2OS cells) and U2OS cells (the monolayer U2OS cells).…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant DNA methylation promotes the self-renewable capacity of ovarian CSLCs [16, 19]. DNA methyltransferase 1 (DNMT1) contributed to the maintenance of stemness of various CSLCs [2025], including OSLCs [10, 11]. According to a study using mammary gland-specific DNMT1-knockout mice, DNMT1 deletion limited the CSLC population and reduced mammary tumorigenesis [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done on cytotoxic activity of VAC extracts and their major compounds [7,[23][24][25]. Several studies have demonstrated that the extracts of VAC showed remarkable cytotoxic activity against various human cancer cell lines [23][24][25]. In this study, besides the extracts, the effect of casticin was also investigated on NRK and HeLa cells.…”
Section: Discussionmentioning
confidence: 99%